Predictive Effects of Immunization and Low Birth Weight on Stunting in Rural Indonesia: A Case Study from Selayar - Musaidah Musaidah; Normalia Normalia; Andi Irmayanti; Noyumala Noyumala (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2025)
Introduction: Stunting continues to be a significant public health challenge in Indonesia, especially in rural regions where access to integrated child health services is limited. This study presents a novel dual variable analysis focusing on two interrelated risk factors immunization status and low birth weight (LBW) which have rarely been examined simultaneously in a rural Indonesian setting. It aims to explore the association between immunization coverage and low birth weight (LBW) and their influence on stunting prevalence among children aged 37 to 72 months in the jurisdiction of the Polebunging Health Center, Selayar Regency. Methods: Employing a cross sectional design, data were collected from 51 children using anthropometric measurements, immunization records, and birth history documentation. The study used WHO growth standards interpreted through Indonesia’s operational framework (the Maternal and Child Health Book, or KIA Book) Results: Findings revealed that 11.8% of the children had incomplete immunization, while 9.8% had a history of LBW. Statistical analysis demonstrated significant associations between both risk factors and stunting (p < 0.05). Children with incomplete immunization were eight times more likely to be stunted, and those with LBW had twelve times higher odds of experiencing growth faltering. These results align with prior literature highlighting the importance of early preventive interventions in child development Conclusion: This study contributes localized, high resolution evidence on the predictive roles of immunization and LBW in rural child stunting, reinforcing the need for integrated maternal and child health strategies. While the sample size and non-random sampling limit generalizability, the findings offer actionable insights for targeted interventions in similar socio epidemiological contexts. Future longitudinal studies are recommended to validate causal relationships and inform scalable public health policies.